Bertahan di Era Distraksi AI: Citra Merek, Sistem Informasi dan Implementasi 5W+1H dalam Membangun Dominasi Brand Top of Mind di Toko Merdeka Stationary - rusyaidi thahery; Yasin Yasin (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2026)
This study aims to determine consumer responses regarding the topic "Surviving the Era of AI Distraction: Implementing Brand Image, Information Systems, and the 5W+1H Framework to Build Top-of-Mind Brand Dominance at Merdeka Stationary." The study employs descriptive statistics, correlation analysis, and multiple linear regression, utilizing a conditional research design. The study population consists of the owner of Merdeka Stationary and a sample of 100 consumers, based on the store's average monthly customer volume. From the owner's perspective, descriptive statistical analysis reveals that all variables are highly influential; however, correlation analysis indicates that only the Brand Image variable shows a significant relationship, while the Information System variable does not. Meanwhile, multiple linear regression analysis shows that the Brand Image, Information System, and 5W+1H Implementation variables all exert a significant influence.